(untitled) (LEGAL DIALOGICA, 2025)
This research aims to analyze the application of the concept of Restorative justice in the resolution of criminal cases in Makassar City. The background of this study is the importance of alternative approaches in law enforcement that prioritize the restoration of relationships between offenders, victims, and society. This research also examines the impact of the implementation of Restorative justice on the efficiency of the criminal justice system, as well as the challenges faced by law enforcement officers in its implementation. The research method used is a normative-empirical juridical approach, with an analysis of relevant laws and regulations and direct interviews with law enforcement officials in Makassar City. The data is analyzed to evaluate the effectiveness, challenges, and opportunities in the implementation of Restorative justice. The results of the study indicate that the implementation of Restorative justice in Makassar City has made a significant contribution to the resolution of criminal cases by reducing recidivism rates and restoring social harmony. However, its implementation still faces challenges such as lack of public understanding, and differing perceptions among law enforcement officers. This study recommends the need for intensive training for officers, increased public awareness, and strengthened regulations to support the successful implementation of Restorative justice. Abstrak: Penelitian ini bertujuan untuk menganalisis penerapan konsep Restorative justice dalam penyelesaian perkara pidana di Kota Makassar. Latar belakang penelitian ini adalah pentingnya pendekatan alternatif dalam penegakan hukum yang mengutamakan pemulihan hubungan antara pelaku, korban, dan masyarakat. Penelitian ini juga mengkaji dampak pelaksanaan Restorative justice terhadap efisiensi sistem peradilan pidana serta kendala yang dihadapi oleh para penegak hukum dalam implementasinya. Metode penelitian yang digunakan adalah yuridis normatif-empiris, dengan pendekatan analisis terhadap peraturan perundang-undangan yang relevan serta wawancara langsung dengan aparat penegak hukum di Kota Makassar. Data dianalisis untuk mengevaluasi efektivitas, tantangan, dan peluang dalam pelaksanaan Restorative justice. Hasil penelitian menunjukkan bahwa pelaksanaan Restorative justice di Kota Makassar memberikan kontribusi signifikan terhadap penyelesaian perkara pidana dengan mengurangi tingkat residivisme dan memulihkan keharmonisan sosial. Namun, implementasinya masih menghadapi kendala, seperti kurangnya pemahaman masyarakat, serta perbedaan persepsi di kalangan aparat hukum. Penelitian ini merekomendasikan perlunya pelatihan intensif bagi aparat, peningkatan kesadaran publik, dan penguatan regulasi untuk mendukung keberhasilan penerapan Restorative justice.